Conception de la commande d’un pont roulant par API - Sofiane Sehairi; Darem EL Moradj (Université Amar Thelidji- Laghouat.FACULTE : TECHNOLOGIE.DEPARTEMENT : ELECTROTECHNIQUE, 2022)
The work presented in this thesis is essentially based on the use of the programmable logic controller (PLC) for the control of a double-girder overhead crane using the LADDER programming language which is the language most used for electrical diagrams. After having found the control diagram of the double-girder overhead crane according to a given specification and the available equipment; the control must be designed and simulated.